Pelatihan Strategi Pengerjaan TOEFL Test Bagian Listening kepada Siswa Kelas XI SMAN Jatinangor Sumedang - Sakina, Rahma; Taufik, Muhammad Fikri (Ma'soem University, 2023)
Having a fluent Enlish skill is necessary for students because this skill can support their study and career in the future. One of ways to measure one’s English skill accurately is through TOEFL test. Listening is one of skills that will be assessed in the TOEFL test and many students consider that listening is hard. Therefore, this training is aimed at improving students’ knowledge of some strategies in answering TOEFL test, especially in listening skill. The method used in this community service is Asset Based Community Development. The data results show that most of participants could understand the strategies of answering TOEFL test, listening section and they could apply them in answering the questions very well.